Sound tracks : popular music, identity, and place - Connell, John, 1946- (Critical geographies ;, 2003)
"Sound Tracks is the first comprehensive book on the new geography of popular music, examining the complex links between places, music and cultural identities. It provides an interdisciplinary perspective on local, national and global scenes, from the 'Mersey' and 'Icelandic' sounds to 'world music', and explores the diverse meanings of music in a range of regional contexts." "Sound Tracks traces the ways in which music has informed complex globalisations, the role of companies and technology in diffusion, innovation and commercialism and the wider significance of cultural industries. It links migration and mobility to new musical practices, whether in 'developing' countries of metropolitan centres, and traces the recent rise of 'music tourism'. It examines issues of authenticity and credibility, and the quest for roots within different musical genres, from buskers to brass bands, and from rap to rai. Sound Tracks emphasises music's contributions to the contradictions, illusions and celebrations of contemporary life. It situates music and the music industry within spatial theories of globalisation and local change: fixity and fluidity entangled." "In a world of intensified globalisation, links between space, music and identity are increasingly tenuous, yet places give credibility to music, not least in the 'country', and music is commonly linked to place, through claims to tradition, 'authenticity' and originality, and as a marketing device. This book develops new perspectives on these relationships and how they are situated within cultural and geographical thought."--Jacket